Frequency of Asymptomatic Bacteriuria in Patients with Preterm Labor - Aleem, Samana; Lakhan, Hazooran; Karamat, Shahida; Jabbar, Asifa Abdul; Farooq, Saima; Sheikh, Farheen (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine the frequency of asymptomatic bacteriuria in patients presenting in preterm labor in a tertiary care hospital Methodology: This Cross-sectional study was conducted at Department of Obstetrics & Gynecology, Peer Syed Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat from July to December 2018. A total of 115 women with preterm labour were included in this study through Non probability consecutive sampling technique. Clean voided mid-stream urine specimen of patients was collected. Subjects were adequately educated to prevent contamination of specimen. The specimen was collected into sterilized wide, necked, leak proof, plastic containers. The patients were followed for outcome of preterm labour. SPSS v. 20 was used to enter and analyses the data. Results: The average age of patients was 31.94±5.26 years. The mean gestational age at delivery was 32±3.61 weeks. Frequency of asymptomatic bacteriuria was 27.83%. Conclusion: It has been concluded that a rate of asymptomatic bacteriuria can be observed among pregnant females admitted with preterm labour. The hazardous consequences related to asymptomatic bacteriuria can be minimized by prescribing a course of antimicrobials in early pregnancy. Key Words: Urinary tract infection, asymptomatic bacteriuria, Preterm labor.